Ser252Asn Mutation Introduces a New N-Linked Glycosylation Site and Causes Type IIb Protein C Deficiency - Zhou, Shijie; Wu, Xi; Song, Ying; Li, Lei; Shi, Chunli; Lai, Zhe; Ding, Qiulan; Wu, Wenman; Dai, Jing; Wang, Xuefeng; Lu, Yeling (Thrombosis and Haemostasis, 2023)
Background Protein C (PC) is a vitamin K-dependent anticoagulant serine protease zymogen which upon activation by the thrombin–thrombomodulin (TM) complex downregulates the coagulation cascade by degrading cofactors Va and VIIIa by limited proteolysis. We identified a thrombosis patient who carried a heterozygous mutation c.881G > A, p.Ser252Asn (S252N) in PROC. This mutation was originally described in a report of novel mutations in patients presenting with defective PC anticoagulant activity in Paris. The research identified PC-S252N (the “Paris” mutation) in a propositus and her family members and highlighted the critical role of Ser252 in the anticoagulation process of activated PC (APC).Material and Methods We expressed the PC-S252N mutant in mammalian cells and characterized the properties in coagulation assays to decipher the molecular basis of anticoagulant defect of this mutation.Results We demonstrated that PC-S252N had a diminished ability to TM binding, which resulted in its impaired activation by the thrombin-TM complex. However, APC-S252N exhibited a slightly stronger cleavage capacity for the chromogenic substrate. Meanwhile, the catalytic activity of APC-S252N toward FVa was significantly reduced. Sequence analysis revealed that Ser252 to Asn substitution introduced a new potential N-linked glycosylation site (252NTT254) in the catalytic domain of PC, which adversely affected both the activation process of PC and anticoagulant activity of APC.Conclusion The new N-glycosylation site (252NTT254) resulting from the mutation of Ser252 to Asn252 in PROC affects the overall structure of the protease, thereby adversely affecting the anticoagulant function of protein C. This modification has a negative impact on both TM-promoted activation of protein C and APC cleavage of FVa, ultimately leading to thrombosis in the patient.
Keywords: protein C; mutation; anticoagulant; thrombosis; glycosylation